Optimization of N‑Benzoylindazole Derivatives as Inhibitors of Human Neutrophil Elastase - Crocetti, Letizia; Schepetkin, Igor A; Cilibrizzi, Agostino; Graziano, Alessia; Vergelli, Claudia; Giomi, Donatella; Khlebnikov, Andrei I; Quinn, Mark T; Giovannoni, Maria Paola (Journal of medicinal chemistry, 2013)
Human neutrophil elastase (HNE) is an important therapeutic target for treatment of pulmonary diseases. Previously, we identified novel N-benzoylindazole derivatives as potent, competitive, and pseudoirreversible HNE inhibitors. Here, we report further development of these inhibitors with improved potency, protease selectivity, and stability compared to our previous leads. Introduction of a variety of substituents at position 5 of the indazole resulted in the potent inhibitor 20f (IC50 ∼10 nM) and modifications at position 3 resulted the most potent compound in this series, the 3-CN derivative 5b (IC50 = 7 nM); both derivatives demonstrated good stability and specificity for HNE versus other serine proteases. Molecular docking of selected N-benzoylindazoles into the HNE binding domain suggested that inhibitory activity depended on geometry of the ligand–enzyme complexes. Indeed, the ability of a ligand to form a Michaelis complex and favorable conditions for proton transfer between Hys57, Asp102, and Ser195 both affected activity.